Hidden children of the Holocaust Belgian nuns and their daring rescue of young Jews from the Nazis - Vromen, Suzanne; Oxford eBooks (Oxford : Oxford University Press, 2008)
In Belgium in the summer of 1942, when the Nazis began the brutal roundup of Jewish families, parents searched desperately for safe havens for their children. This book tells the stories of children who found haven in Roman Catholic convents and orphanages, and of the women who sheltered them.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jewish children in the Holocaust -- Belgium; World War, 1939-1945 -- Jews -- Rescue -- Belgium; Hidden children (Holocaust) -- Belgium; Christianity and antisemitism -- Belgium -- History -- 20th century; Holocaust survivors -- Interviews; Belgium -- History -- German occupation, 1940-1945.; Electronic books